2019
DOI: 10.1016/j.neuron.2019.01.048
|View full text |Cite
|
Sign up to set email alerts
|

RNA Binding Antagonizes Neurotoxic Phase Transitions of TDP-43

Abstract: Highlights d optoTDP43 is a light-inducible model of TDP-43 proteinopathy and is neurotoxic d RNA binding antagonizes aberrant liquid-liquid phase separation (LLPS) of TDP-43 d Acute recruitment to RNA-containing stress granules maintains TDP-43 solubility d TDP-43 targeting oligonucleotides prevent aberrant LLPS and rescues neurotoxicity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

43
486
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(551 citation statements)
references
References 67 publications
43
486
1
Order By: Relevance
“…within the TDP43 C-terminus promotes liquid-phase separation and aggregation (90)(91)(92)(93)(94). Even so, our observations and those of others (64,65) show that sTDP43 is relatively insoluble and prone to aggregation, despite lacking the LCD.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…within the TDP43 C-terminus promotes liquid-phase separation and aggregation (90)(91)(92)(93)(94). Even so, our observations and those of others (64,65) show that sTDP43 is relatively insoluble and prone to aggregation, despite lacking the LCD.…”
Section: Discussionsupporting
confidence: 67%
“…In keeping with previous studies 65 , overexpressed sTDP43 accumulates in the cytoplasm where it often forms large, insoluble inclusions. The low-complexity domain (LCD) within the TDP43 C-terminus is essential for liquid-phase separation [87][88][89][90] , and has been heavily implicated in TDP43 aggregation. Even so, our observations and those of others 64,65 show that sTDP43 is insoluble and prone to aggregation, despite lacking the LCD.…”
Section: Discussionmentioning
confidence: 99%
“…RNA also appears to play an important role in the formation of these structures. Indeed, RNA itself undergoes phase transition (Jain & Vale, 2017) and has been shown to promote phase transitions of several proteins (Lin et al, 2015;Molliex et al, 2015;Zhang et al, 2015), including Tau (Zhang et al, 2017), and also to inhibit protein aggregation, most notably of Fused in Sarcoma, FUS and TDP-43 (Burke et al, 2015;Mann et al, 2019;Shelkovnikova et al, 2014). Recently, Maharana et al, showed that for several prion-like proteins, including FUS, these disparate effects can be explained by the ratio of protein to RNA; where excess of RNA promotes solubility and decreased amount of RNA induces phase-transition (Maharana et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Microinjection of RNase A can induce aggregation of nuclear FUS protein in vivo, suggesting that, in this case, high levels of RNA oppose phase separation. RNA binding-defective mutants of TDP-43 display an increased propensity to phase separate in vitro and in vivo and addition of TDP-43 RNA substrates allows TDP-43 to remain soluble (Maharana et al, 2018;J. R. Mann et al, 2019).…”
Section: Introductionmentioning
confidence: 99%